Elasticity Properties of Pulmonary Artery in Patients with Bicuspid Aortic Valve. Issue 6 (5th December 2013) - Celik, Murat; Yuksel, Uygar Cagdas; Yalcinkaya, Emre; Gokoglan, Yalcin; Yildirim, Erkan; Bugan, Baris; Kaya, Erkan; Gungor, Mutlu
<x xml:space="preserve">Abstract</x> Objective Although the vascular complications of bicuspid aortic valve (BAV) disease cause significant morbidity and mortality, the role of pulmonary artery in this pathogenesis is less understood. We aimed to assess the elastic properties of pulmonary artery with echocardiography in patients with BAV. Material and Methods Thirty patients with BAV (26 males) were enrolled in this study. The presence of aortic stenosis was accepted as exclusion criteria. Thirty‐two healthy subjects (27 males) with no any history of cardiovascular disease comprised the control group. In all patients, maximal frequency shift (MFS) and acceleration time (AcT) of the pulmonary artery flow trace were measured echocardiographically in parasternal short‐axis view. Subsequently, pulmonary artery stiffness (PAS) was calculated by using the following formula PAS (kHz/sec) = MFS/AcT. Results There were no significant differences in baseline demographic characteristics of the study population. Aortic strain and aortic distensibility index were lower, and aortic stiffness index (SI) higher, in patients with BAV. The PAS was significantly increased in patients with BAV compared with control subjects with tricuspid aortic valve (11.08 ± 2.27 vs. 7.11 ± 1.54, P < 0.001). There was a significant correlation between aortic diameters, aortic elasticity indexes, and PAS. Multivariate linear regression analysis, the only significant independent factor affecting the PAS was SI (β = 0.547, P < 0.001). Conclusion We demonstrated that elastic properties of pulmonary artery tend to be impaired as in the aorta in patients with BAV disease.